“Obutchénie” na perspectiva desenvolvimental: sua recepção e apropriação na literatura psicológica-didática latino-americana - Lima, Juliana de Assis (2023)
This dissertation addresses the reception and appropriation movement of the Russian term and/or concept obutchénie (обучение) in Latin American psychological-didactic literature, particularly within the works of representatives of Developmental Learning Theory. The analysis was carried out based on the concept, content, structure, function, and method assumed by the Theory of Study Activity, as well as in relation to the notion of the subject that supports it or emerges from the developmental perspective. The research engaged with authors whose works adopt the term and/or concept obutchénie, including translations directly from Russian. The general objective was to analyze the conceptualization adopted by the term obutchénie (обучение) within Historical-Cultural Psychology, specifically within Developmental Learning Theory, in the Soviet context and its reception in Latin American psychological-didactic literature. The specific objectives were: to describe the process of constitution and consolidation of Developmental Learning Theory in the Latin American context, taking as reference the Elkonin-Davidov-Repkin system responsible for the elaboration of the Theory of Study Activity; to identify how this theory reached Brazil, through whom, how and when it disseminated, and how the process of reception and interpretation has been; finally, to analyze the reception of the Russian term and/or concept obutchénie (обучение) from five different perspectives: (a) from the perspective of teaching (instruction); (b) from the perspective of learning (to learn); (c) from the perspective of teaching-learning; (d) from the perspective of the transliterated Russian term obutchénie; (e) from the perspective of collaborative developmental learning. This research is of a theoretical nature and develops interpretations based on evidence taken from the thought of Latin American researchers analyzed in relation to the term and/or concept obutchénie (обучение), through the documentary analysis of a sample of their works. In this sense, it is a study that distances itself from positivist methodological assumptions because it starts from the idea that, although objective factual material has been used, its approach respects constructive and hypothetical principles. The research also intended to present the particular interpretations of researchers dedicated to this developmental approach, as well as the criteria they used during the process of translation and reception of the Russian term and/or concept obutchénie (обучение), in order to assist Brazilian researchers in understanding this movement, the divergences of interpretations that exist, and during the stage of making their own choices. We have made ours: we are in favor of using the term "collaborative developmental learning" when referring to the Russian term and concept obutchénie (обучение) in the sense of a specific form of didactic organization of learning aimed at the psychological development of the subject studying.